SYNTHESIS OF BISCOUMARIN DERIVATIVES AS ANTIMICROBIAL AGENTS - MURATOVIĆ, SAMIJA; DURIĆ, KEMAL; VELJOVIĆ, ELMA; OSMANOVIĆ, AMAR; SOFTIĆ, DŽENITA; ZAVRŠNIK, DAVORKA (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: As a further part of our chemical and biological studies in this field, we describe the preparations of the properly substituted benzylidene-bis-(4-hydroxycoumarin) derivatives 5a-h and 3-(6-oxo-(1H)-benzopyrano[4,3-b]benzopyran-7-yl)-4-hydroxycoumarin derivatives 6a-e. Methods: The synthesized compounds were screened for their in vitro antimicrobial activity against five strains of bacteria and two fungal strains using disk diffusion assay and dilution method. The way in which the substituent group's physicochemical properties influence the antimicrobial activity is discussed in the paper. Results: The in vitro evaluation of their inhibitory properties towards five strains of Gram-positive and Gram-negative bacteria and two fungal strains indicated that the 4-trifluoromethylbenzylidene derivative of bis-(4-hydroxycoumarin) (compound 5c) and 3-(6-oxo-(1H)-18-bromobenzopyrano[4,3-b]benzopyran-7-yl)-4-hydroxycoumarin derivative (compound 6b) possess the most potent antibacterial activities, with MIC of 3.9 μg/mL - 7.8 μg/mL against Gram-positive bacteria. Conclusion: The compound 6b has greater antibacterial activity than the standard chloramfenicol (inhibition zone 26 mm and MIC 1.9 μg/mL) against Staphyloccocus aureus and could be considered as leading compound in the future antimicrobial drug development. Key words: Benzylidene-bis-(4-hydroxycoumarin), benzopyranocoumarin derivatives, antibacterial assays, antifungal activity.